Tahfidz's Curriculum in SDIT Al-Islam Sine Ngawi Based on Boarding School - Aziz Nuri Satriyawan; Kartika Sunarso; Fina Hanifah (Al-Adzka: Jurnal Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2022)
The research was based on the fact that some students who did not achieve the target of Tahfidz Qur'an at the Sekolah Dasar Islam Terpadu (SDIT) Al-Islam Sine Ngawi, East Java. The purpose of this research is the implementation of Tahfidz Qur'an learning and the students’ problem in not achieving the Tahfidz Qur'an target at SDIT Al-Islam Sine Ngawi. The research implementation uses a qualitative approach with case study research. Informants in this research are students, school principals, and Tahfidz teachers. Observation, interviews, and documentation are used in collecting the data. The results of the research are first, the implementation of Tahfidz Qur'an is carried out every day after the dhuha prayer in the congregation. The implementation of Tahfidz Qur’an starts with several learning activities, they are; pre-activity, while activity and post activity which  refer to lesson plan for the Tahfidz Qur'an subject. The assessment of Tahfidz Qur'an is the quantity of memorization, makrorijul hurf, and the science of recitation (tajwid). Second, the inhibiting factors that affect the inability of students in memorizing the Al-Qur'an are the different qualifications of students for memorizing the Qur'an and lack of the parental role.